Whose waters? large-scale agricultural development and water grabbing in the Wami-Ruvu River Basin, Tanzania - Eeden, A. van; Mehta, L.; van Koppen, Barbara (2016)
In Tanzania like in other parts of the global South, in the name of 'development' and 'poverty eradication' vast tracts of land have been earmarked by the government to be developed by investors for different commercial agricultural projects, giving rise to the contested land grab phenomenon. In parallel, Integrated Water Resources Management (IWRM) has been promoted in the country and globally as the governance framework that seeks to manage water resources in an efficient, equitable and sustainable manner. This article asks how IWRM manages the competing interests as well as the diverse priorities of both large and small water users in the midst of foreign direct investment. By focusing on two commercial sugar companies operating in the Wami-Ruvu River Basin in Tanzania and their impacts on the water and land rights of the surrounding villages, the article asks whether institutional and capacity weaknesses around IWRM implementation can be exploited by powerful actors that seek to meet their own interests, thus allowing water grabbing to take place. The paper thus highlights the power, interests and alliances of the various actors involved in the governance of water resources. By drawing on recent conceptual insights from the water grabbing literature, the empirical findings suggest that the IWRM framework indirectly and directly facilitates the phenomenon of water grabbing to take place in the Wami-Ruvu River Basin in Tanzania.